Toddlers Prefer Adults as Informants: 2‐ and 3‐Year‐Olds' Use of and Attention to Pointing Gestures From Peer and Adult Partners. Issue 4 (28th January 2021) - Kachel, Gregor; Moore, Richard; Hepach, Robert; Tomasello, Michael
Abstract : Two‐ and 3‐year‐old children ( N  = 96) were tested in an object‐choice task with video presentations of peer and adult partners. An immersive, semi‐interactive procedure enabled both the close matching of adult and peer conditions and the combination of participants' choice behavior with looking time measures. Children were more likely to use information provided by adults. As the effect was more pronounced in the younger age‐group, the observed bias may fade during toddlerhood. As there were no differences in children's propensity to follow peer and adult gestures with their gaze, these findings provide some of the earliest evidence to date that young children take an interlocutor's age into account when judging ostensively communicated testimony.